The Effect of Working Capital Turnover and Cash Turnover on Profitability Before and During the Covid-19 Pandemic in Health Sector Companies Listed on the Indonesian Stock Exchange - Fitrianingsih, Nur Ary (Tax Accounting Applied Journal, 2024)
The Covid-19 pandemic has increased demand in the health sector. This study aims to determine and analyze the differences in working capital turnover, cash turnover, and profitability and analyze whether there is an effect of turnover of working capital and turnover of cash on the profitability between before and during the Covid-19 pandemic in health sector companies listed on the Indonesia Stock Exchange. A total of 17 companies were used as research samples using purposive sampling method. To analyze the data using t-test and multiple linear regression. In health sector companies listed on the Indonesia Stock Exchange, this study shows no difference in working capital turnover, cash turnover, or profitability between before and during the Covid-19 pandemic. Working capital turnover and cash turnover have a negative effect on profitability before and during the Covid-19 pandemic.Keywords: Working Capital Turnover, Cash Turnover Profitability